Digital business roadmap webinar: Exploring creative digital business idea - Artika Arista; Muhammad Eka Purbaya; Khairun Nisa Meiah Ngafidin (Universitas Muhammadiyah Magelang, 2021)
In facing the industrial era 4.0, college graduates in information and computer science are required to adapt to the developments and needs of current industrial technology. The link and match between the world of education and industry is the key to optimizing the absorption of skilled labor. To answer these challenges, the Information systems undergraduate study program at Institut Teknologi Telkom Purwokerto, SUHU, and T-Lab held a Webinar Series